PENGARUH BLENDED LEARNING BERBANTU GOOGLE CLASSROOM TERHADAP HASIL BELAJAR PADA MATERI VIRUS - sukmawati syam; Khaerati (Universitas Cokroaminoto Palopo, 2022)
This study aims to determine the effect of the use of Google Classroom-assisted Blended Learning on student learning outcomes on viral material at SMAN 4 Luwu. This research is a quasi-experimental study with a nonequivalent control group design. The population in this study amounted to 186 students. The sample of this research is class X MIPA 5 and X MIPA 6 each totaling 31 students who were selected by purposive sampling. The data collection technique was carried out by learning outcomes tests. Data analysis used descriptive and inferential statistical analysis, namely normality test, homogeneous test and independent sample t test. The results of the descriptive test obtained the average value in the experimental class which was 84.68 while in the control class the average value obtained was 81.81. The results of the analysis of hypothesis testing are 0.043 <0.05, it is concluded that there is an effect of using the Google Classroom-assisted Blended Learning learning model on student learning outcomes in class X virus material at SMAN 4 Luwu.